2015
DOI: 10.11607/ofph.1452
|View full text |Cite
|
Sign up to set email alerts
|

Noxious Stimulation of the Rat Tooth Pulp May Impair Learning and Memory Through the Induction of Hippocampal Apoptosis

Abstract: Memory and learning impairment induced by noxious stimulation of the rat tooth pulp may be correlated with activation of apoptotic pathways in the hippocampus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Capsaicin‐induced orofacial pain causes learning and memory impairment in rats (Raoof et al . ,b, Kooshki et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Capsaicin‐induced orofacial pain causes learning and memory impairment in rats (Raoof et al . ,b, Kooshki et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…The effects were inhibited by ibuprofen pre‐treatment (Raoof et al . ,b). Orexin‐A projections and orexin receptors have been found within the areas of the brainstem that are involved in nociception processing (Azhdari‐Zarmehri et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although several researches support the association between chronic pain and impaired cognitive function, a small portion of them are focused on orofacial pain. Two studies recently showed that capsaicin-induced pulpal pain is associated with impairment of learning and memory, and neuronal apoptosis in hippocampus of rats ( Raoof et al, 2015a ; Raoof et al, 2015b ).…”
Section: Introductionmentioning
confidence: 99%